ANALYSIS OF THE FACTORS AFFECTING THE COMMITMENT OF THE HEAD OF THE BUMDESA IN BOGOR REGENCY - Herman Herman; Yayan Hadiyat (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2022)
ABSTRACTThis study aims to examine and analyze the indicators that influence the commitment to the organization of the Head of BUMDesa in Bogor Regency, using a questionnaire that has been tested for validity and reliability as many as 30 respondents from 131 people, with the verification method carried out through the method and analysis of the Structural Equation model. Based on the results, it can be concluded that affective commitment is the most dominant indicator in influencing commitment to the organization of the head of BUMDesa in Bogor Regency. Meanwhile, the lowest score is normative commitment. Based on the results of this study, the suggestion that can be given is that the head of BUMDesa must increase Normative Commitment through strengthening indicators of having an obligation to the organization and loyalty to the organization. The activities that can be carried out are when the head of BUMDesa is elected, an orientation and job introduction program and the position of the Head of BUMDesa must be carried out or in the form of pre-service activities for the head of BUMDesa.ABSTRAKTujuan penelitian ini adalah untuk mengkaji dan menganalisis indikator-indikator yang mempengaruhi komitmen organisasi Kepala BUMDesa di Kabupaten Bogor, dengan menggunakan kuesioner yang telah diuji validitas dan reliabilitasnya sebanyak 30 responden dari 131 orang, dengan metode verifikasi dilakukan melalui metode dan analisis model Structural Equation. Berdasarkan hasil uji analisis dapat disimpulkan bahwa komitmen afektif merupakan indikator yang paling dominan dalam mempengaruhi Komitmen Organisasi kepala BUMDesa di Kabupaten Bogor. Sedangkan skor terendah adalah komitmen normatif. Saran yang dapat diberikan adalah kepala BUMDesa harus meningkatkan komitmen normatif melalui penguatan indikator memiliki kewajiban terhadap organisasi dan loyalitas terhadap organisasi. Kegiatan yang dapat dilakukan adalah pada saat pemilihan kepala BUMDesa harus dilakukan program orientasi dan pengenalan pekerjaan dan jabatan Kepala BUMDesa atau berupa kegiatan prajabatan kepala BUMDesa.